Intestinal allergic inflammation in birch pollen allergic patients in relation to pollen season, IgE sensitization profile and gastrointestinal symptoms. Issue 1 (30th May 2014) - Rentzos, Georgios; Lundberg, Vanja; Stotzer, Per‐Ove; Pullerits, Teet; Telemo, Esbjörn
Abstract: Background: Birch pollen allergic patients frequently experience gastrointestinal upset accompanied by a local allergic inflammation in the small intestine especially during the pollen season. However, it is not known if the GI pathology is connected to the subjective symptoms of the patient. The objective of this study was to evaluate the immune pathology of the duodenal mucosa and the serum IgE antibody profiles in birch pollen allergic patients in relation to their gastrointestinal symptoms, during and outside the birch pollen season. Methods: Thirty‐two patients with birch pollen allergy and sixteen healthy controls were enrolled in the study. Twenty allergic patients had gastrointestinal symptoms and twelve did not. All participants underwent an allergy investigation and gastroscopy with duodenal biopsy. The duodenal biopsies were retrieved during the pollen season (May‐June) and off‐season (November‐March). The biopsies were immunostained for mast cells (IgE and tryptase), eosinophils, T cells (CD3), and dendritic cells (CD11c). Pollen‐specific IgE antibodies were determined by ImmunoCAP and component microarray (ISAC). Results: Patients in both pollen allergic groups showed similar degree of intestinal allergic inflammation during the pollen season regardless of gastrointestinal symptoms. The eosinophils, mast cells and dendritic cells were increased in the mucosa. Patients with gastrointestinal symptoms had significantly elevated IgE antibodies to birch (rBet v 1), hazelnut (rCor a 1), and apple (rMal d1) during the pollen season. Conclusions: Patients allergic to birch pollen have clear signs of an ongoing allergic inflammation in their intestinal mucosa, which is aggravated during the pollen season. The magnitude of the allergic intestinal inflammation is not associated with subjective gastrointestinal symptoms of the individual patient.